2020
DOI: 10.1002/cam4.3322
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00857 regulates the progression and glycolysis in ovarian cancer by modulating the Hippo signaling pathway

Abstract: Ovarian cancer is one of the most common gynecological cancers with high morbidity and mortality, which seriously endangers women's health and quality of life. Long noncoding RNAs (lncRNAs) can regulate the progression of cancers, including ovarian cancer. LINC00857 (long intergenic non‐protein coding RNA 857) has been discovered to be a crucial factor in the regulation of cancer development. Nevertheless, the specific functions and mechanisms of LINC00857 in ovarian cancer remain unclear. The Hippo signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…Ovarian cancer (OV) is the fifth most common type of cancer affecting women worldwide, particularly women aged >65 years (1,2). OV is a type of gynecological cancer that is associated with a high morbidity and mortality, severely compromising women's health and quality of life (3,4). Radical surgery and chemotherapy are considered as two important methods for treating OV, but these methods do not appear to reduce the high recurrence rate of OV or improve the prognosis of the patient with OV (5).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OV) is the fifth most common type of cancer affecting women worldwide, particularly women aged >65 years (1,2). OV is a type of gynecological cancer that is associated with a high morbidity and mortality, severely compromising women's health and quality of life (3,4). Radical surgery and chemotherapy are considered as two important methods for treating OV, but these methods do not appear to reduce the high recurrence rate of OV or improve the prognosis of the patient with OV (5).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have indicated that LINC00857 acts as a miRNAs sponge to regulate tumour progression 20,21 . Thus, we hypothesize that LINC00857 contributes to Scutellarin‐induced c‐Myc downregulation by binding miRNAs.…”
Section: Resultsmentioning
confidence: 84%
“…MiR-486-5p may target other mRNAs besides IGF1. For instance, YAP1 is targeted by miR-486-5p in ovarian cancer cells [33]. In addition, miR-486-5p may mediate the growth of gastric cancer cells via targeting of PI3KR1 [34].…”
Section: Discussionmentioning
confidence: 99%